Предмет: Алгебра,
автор: Max13264258
а)Упростите выражение(с+2)(с-2)-4с(с-1)
б)Найдите его значение с=0
Ответы
Автор ответа:
0
(с+2)(с-2)-4с(с-1) = с²-4-4с²+4с = -3с²-4+4с.
Если с=0, то -3·0²-4+4·0=-4
Ответ:-4
Если с=0, то -3·0²-4+4·0=-4
Ответ:-4
Автор ответа:
0
А "б"?
Автор ответа:
0
Я написала)
Автор ответа:
0
А сорян Спасибо!)
Похожие вопросы
Предмет: Информатика,
автор: BatmanDoge
Предмет: История,
автор: alinaminova16
Предмет: Химия,
автор: lostanya703
Предмет: География,
автор: MariaRayfish
Предмет: Математика,
автор: Aiza72